Enrichment and source identification of Cd and other heavy metals in soils with high geochemical background in the karst region, Southwestern China. (April 2020) - Wen, Yubo; Li, Wei; Yang, Zhongfang; Zhang, Qizuan; Ji, Junfeng
Abstract: The geographical distributions of Cd and several other metals (Cu, Ni, Pb, Zn, and Cr) were characterized in 308 terra rossa samples across the Guangxi karst region. We found significant enrichments of heavy metals in the saprolites and terra rossa developed in 30 profiles, which is mainly caused by the weathering of Cd-enriched carbonate rocks, while the subsequent pedogenic processes were the dominant factor of the enrichments for Cu, Ni, Pb, Zn, and Cr. Sequential extraction analysis indicated that geogenic Cd and Pb in terra rossa mostly distributed in the residual fractions and exhibited low mobility, whereas the amorphous Fe/Mn oxide fraction was the principal Cd-bearing phase in Cambisols. The good correlation of Fe, Al, and Ti in related bedrocks, saprolites, and terra rossa suggested that in-situ pedogenetic processes provided most of the parent materials for terra rossa. The residual accumulation during the special pedogenesis in the karst region, caused elevated Cd and Pb concentrations with increasing weathering intensity, which was indicated by chemical index of alternation (CIA). In addition, results of Pb isotopic fingerprinting confirmed that terra rossa mainly derived from insoluble residues of underlying carbonate rocks. The allochthonous input of Pb also occurred during pedogenesis, whereas the transport and deposition of non-carbonate materials (clasolite/granite derived soils) was only a minor source to Pb input in terra rossa and the anthropogenic impact seemed to be negligible. Highlights: Geographical and soil type dependent heavy metal distributions in terra rossa were characterized. Sequential extraction results showed that the majority of Cd and Pb was bound in the residual phase. Residual accumulation caused elevated Cd and Pb concentrations with increasing weathering maturity. Naturally allochthonous inputs made relatively minor contribution to metal enrichments.